Have State Institutions Converged Globally? Tracing the Legacy of the “End of History” - Totleben, Bartosz (Ekonomia i Prawo. Economics and Law, 2026)
Motivation: More than thirty-five years ago, Francis Fukuyama published his influential essay “The End of History”, in which he argued that liberal democracy had emerged as the final and most advanced form of political organization. According to this thesis, the ideological evolution of humanity had reached its endpoint, and states around the world would inevitably converge toward democratic governance. Since then, the Berlin Wall has fallen, the Soviet Union has collapsed, new states have been established, and numerous peaceful transitions of power - as well as coups - have taken place. These developments raise a fundamental question: was Fukuyama right? Have we indeed witnessed the “end of history,” or do recent global trends suggest a more complex and contested trajectory? Aim: The main objective of this article is to empirically examine the validity of the “end of history” thesis by assessing whether a global convergence of state institutions toward the model of liberal democracy has occurred. Results: Between 1991 and 2024, sigma-convergence of state institutions was observed across all five dimensions analysed: Electoral Democracy, Liberal Democracy, Participatory Democracy, Deliberative Democracy, and Egalitarian Democracy. The decreasing dispersion of institutional indicators suggests that countries have become more similar in terms of democratic structures. However, this reduction in dispersion does not confirm Fukuyama’s “end of history” thesis. Since 2012, all democracy indexes have shown a consistent downward trend, indicating a global decline in the quality of democratic governance. While decreasing dispersion is evident, it is not accompanied by a universal shift toward liberal democracy. Instead, the data suggest that states are converging toward weaker or more limited forms of democracy (often hybrid or illiberal in nature) challenging the notion of an inevitable ideological endpoint.